Hope level and associated factors among older people living with HIV/AIDS: a cross-sectional study - Yu, Chunlan; Wu, Yan; Zhang, Yuli; Li, Mei; Xie, Xin; Xie, Longsheng (Frontiers in Public Health, 2024)
Background In China, little is known about the hope level of older people living with HIV/AIDS (PLWHA).1 This study was to examine the hope level of older PLWHA in China and identify related factors. Methods This cross-sectional study was conducted in Sichuan province in China among older PLWHA.2 A standardized self-report questionnaire, the Herth Hope Index, was adopted. Multiple linear regression was used to identify factors influencing hope level. p-values <0.05 were considered statistically significant. Results There were 314 participants with an average age of 64.5 (SD ± 8.7). Most of the participants were males (72.6%), primary school and below (65.9%), rural household registration (58.6%) and married (64.3%). More than half of the older adults had pension insurance, had a monthly income of more than RMB 1,000 and considered themselves to be in good health. About 80% confirmed being diagnosed for more than a year and disclosed their HIV status to family and friends. The majority of the population had low medium social support (79%). More than 80% had moderate and severe HIV stigma. Many older PLWHA had medium and high levels of hope, with an average score of 34.31 (SD ± 4.85). Multiple linear regression showed that having pension insurance (β = 1.337, p = 0.015), longer diagnosis (β = 0.497, p = 0.031), better self-reported health (β = 1.416, p<0.001) and higher levels of social support (β = 2.222, p < 0.001) were positively associated with higher levels of hope. HIV stigma (β = −1.265, p < 0.001) was negatively correlated with hope level. Conclusion The hope level of older PLWHA is good, but there is still room for improvement, and its hope is related to multiple factors. Therefore, the AIDS-related healthcare sector should pay special attention to the hope of older PLWHA, help them to improve their health, provide financial assistance and social aid to those with financial difficulties, and take measures to reduce HIV stigma, improve family support for the older adults, and guide the older adults to adopt a positive approach to life.